Room temperature single-step synthesis of metal decorated boron-rich nanowires via laser ablation - Gonzalez-Martinez, Ignacio G.; Bachmatiuk, Alicja; Gemming, Thomas; Cuniberti, Gianaurelio (Giovanni); Trzebicka, Barbara; Rummeli, Mark H. (Nano Convergence, 2019)
Hybrid nanostructures, such as those with nanoparticles anchored on the surface of nanowires, or decorated nanowires, have a large number of potential and tested applications such as: gas sensing, catalysis, plasmonic waveguides, supercapacitors and more. The downside of these nanostructures is their production. Generally, multi-step synthesis procedures are used, with the nanowires and the nanoparticles typically produced separately and then integrated. The few existent single-step methods are lengthy or necessitate highly dedicated setups. In this paper we report a single-step and rapid (ca. 1 min) laser ablation synthesis method which produces a wide variety of boron-rich decorated nanowires. Furthermore, the method is carried at room temperature. The synthesis process consists on a filamentary jet ejection process driven by pressure gradients generated by the ablation plume on the rims of the irradiation crater. Simultaneously nanoparticles are nucleated and deposited on the filaments thus producing hybrid decorated nanowires.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Decorated nanowires; Laser ablation; Nanoparticles; Room temperature; Single step synthesis